Nestor Kirchner – outstanding Argentine President of the XXI century - E. S. Dabaguian (Ибероамериканские тетради)
The article presents the political portrait of Nestor Kirchner, president of Argentina, elected at the beginning of this century. It was a difficult period in the history of one of the biggest countries of Latin America, caused by ruinous default which entailed heavy consequences in all the spheres of social life. Kirchner was in power for only four years, but he left an ineffaceable trace in the people’s memory. His name is inseparably linked with the overcoming of the critical stage and redirecting of the society towards the left-centric development model.